The Impact of Transformational Leadership Practices on Teacher Motivation and School Performance - Kriswanto, Didi; Santosa, Achadi Budi (Journal of Social Studies Arts and Humanities (JSSAH), 2025)
This study aims to examine the role and contribution of transformational leadership in enhancing teachers’ work motivation, particularly in the context of primary education. Using a scoping review approach, this study synthesizes empirical research published between 2020 and 2025, focusing on the relationship between principals’ transformational leadership practices and teacher motivation. The data were collected from open-access academic databases, including Science Direct, Google Scholar, and Open Knowledge Maps, using the keywords “transformational leadership” and “teacher work motivation.” The review identified seven relevant empirical studies that consistently demonstrate a positive and significant influence of transformational leadership on teachers’ motivation and performance. The analysis highlights four key dimensions of transformational leadership that contribute to improving teacher motivation: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Effective principals inspire teachers through vision, emotional engagement, intellectual encouragement, and personal attention, thereby fostering professional growth and organizational commitment. The findings emphasize that the better the implementation of transformational leadership, the higher the teachers’ motivation and work satisfaction, ultimately improving school effectiveness and educational outcomes.